ANALISIS PELATIHAN, OCB (ORGANIZATIONAL CITIZENSHIP BEHAVIOR), REMUNERASI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING TERHADAP KINERJA KARYAWAN - nurmala mustika dewi (Universitas Riau Kepulauan, 2019)
AbstractThis study aims to analyze the training, organizational citizenship behavior (OCB), remuneration with job satisfaction as an intervening variable on employee performance. Research responden are the employees PT. Bank BTN Batam of 82 respondents with sampling using slovin formula. Sources and data collection tecniques used in this study are primary data, to wit data obtained or collected directly from the sources data through interviews and a list of questions given to the responden. The result of the analysis of training, OCB, remuneration on employee performance with job satisfaction as intervening variable. The results showed that the training had positive and insignificant effect on job satisfaction. OCB has positive and insignificant effect on job satisfaction. Remuneration has a positive and insignificant effect on job satisfaction. Training has a positive and insignificant effect on employee performance. Remuneration has positive and insignificant effect on employee performance and job satisfaction have positive and significant effect to employee performance. The data analysis used SEM (Structural Equation Modelling) with PLS program. KeywordsTraining, Organizational Citizenship Behavior (OCB), Remuneration, Job Satisfaction, Employee Performance